(untitled) (Psychology Travelogs, 2024)
The article is dedicated to the pressing issue of ensuring the psychological resilience of combatants. The paper provides an overview of the factors leading to the disruption of psychological resilience in combatants due to their involvement in combat actions in the russo-Ukrainian War. It outlines the characteristic features of their psychophysical states and their impact on the development of maladaptive processes in the military personnel. Various methods of restoring the psychological resilience of combatants through psychosocial adaptation are described. The purpose of this article is to provide a theoretical justification of the peculiarities of the process of maintaining psychological resilience in individuals who have participated in combat actions. The article emphasizes that besides the economic, political, and social consequences of war for society, there are also psychological repercussions for individuals, especially those directly involved in combat. It is noted that the impact of war factors on the human psyche is extremely diverse. Importantly, it is highlighted that softer and delayed consequences of combat significantly outweigh the immediate effects, influencing not only the physical and mental health of military personnel but also their psychological resilience, stability of values, and worldview. It is emphasized that the primary goal of psychologists in the process of psychological support is to contribute to optimizing psychosocial adaptation and conducting psychological rehabilitation for participants in combat actions. The author argues that adaptation work with combatants involves the use of various methods, such as social, psychological, pedagogical, legal, medical, financial-economic, informational, and labor-related. It has also been highlighted that optimizing the interaction between the psychologist and the combatant should occur at both individual and group levels, as well as within the community.